Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Total synthesis of pulchellalactam via an RCM strategy - Chavan, Subhash P.; Pathak, Ashok B.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthetic Communications, 2007)
Total synthesis of (Z) pulchellalactam, a CD protein tyrosine phosphatase inhibitor, from commercially available methallyl chloride employing ring-closure metathesis (RCM) as a key step is described.
Keywords: alkaloid; Natural products; pulchellalactam; RCM; Total synthesis

Tandem aza-michael-condensation-aldol cyclization reaction: approach to the construction of DE synthon of (+/-)-camptothecin - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synlett, 2008)
An efficient synthesis of the DE ring of camptothecin, employing a Reformatsky and a tandem one-pot, three-step transformation involving aza-Michael reaction, condensation with ethyl malonyl chloride followed by intramolecular `aldol' reaction to furnish the dihydropyridone derivative from commercially available starting materials, has been achieved.
Keywords: Aldol cyclizations; alkaloids; antitumor; Natural products; Reformatsky reaction

Total syntheses of D-allo-1-deoxynojirimycin and L-talo-1-deoxynojirimycin via reductive cyclization - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (RSC Advances, 2014)
Synthesis of a polyhydroxypiperidine framework for L-talo-1-deoxynojirimycin and D-allo-1-deoxynojirimycin was achieved from L-tartaric acid by employing flash dihydroxylation and reductive lactamisation as the key steps.

Total synthesis of (R)-lipoic acid and (S)-lipoic acid via an Mn (III)-salen-catalyzed oxidative kinetic resolution - Purude, Abhijeet N.; Pawar, Kailash P.; Patil, Niteen B.; Kalkote, Uttam R.; Chavan, Subhash P. (Tetrahedron-Asymmetry, 2015)
The asymmetric synthesis of both the antipodes of alpha-lipoic acid is described. The total synthesis of racemic and asymmetric lipoic acid is achieved from propane 1,3-diol. This work reports the use of Mn (III)-salen-catalyzed oxidative kinetic resolution as the key step to obtain enantiomerically pure (R)- and (S)-lipoic acid. The undesired product formed during the resolution can be recycled to achieve the desired isomer. (C) 2015 Elsevier Ltd. All rights reserved.

Total synthesis of (+/-)-quinagolide: a potent D-2 receptor agonist for the treatment of hyperprolactinemia - Chavan, Subhash P.; Kadam, Appasaheb L.; Kawale, Sanket A. (ACS Omega, 2019)
A potent dopamine (D-2) receptor agonist (+/-)-quinagolide, which is used for the treatment of hyperprolactinemia, was synthesized using the ring closing metathesis (RCM) approach from meta-hydroxybenzaldehyde as the starting material. The key features of this synthesis are pyrolytic elimination, late-stage expedient synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates from olefin 6, via conjugate addition-elimination upon acetate 11, followed by RCM and phenyliodine bis(trifluoroacetate) (PIFA)-mediated Hofmann rearrangement of piperidine-3-carboxamide, which enables the synthesis of 3-aminopiperidine skeleton of quinagolide. For the total synthesis of natural products such as ergot alkaloids, late-stage synthesis of functionalized trans-fused tetrahydropyridine-3-carboxylates using RCM and PIFA-mediated Hofmann rearrangement of piperidine-3-carboxamide, which allows quick access to the synthetically challenging 3-aminopiperidine skeleton, are the main achievements of the present work.